2023
DOI: 10.1002/cpp.2860
|View full text |Cite
|
Sign up to set email alerts
|

The Arab COVID‐19 Anxiety Syndrome Scale (C‐19ASS): COVID‐19 anxiety syndrome and psychological symptoms in the Saudi Arabian population

Abstract: IntroductionThe COVID‐19 Anxiety Syndrome Scale (C‐19ASS) is a reliable scale assessing dysfunctional coping strategies activated in response to COVID‐19 fear and threat. The present study aimed to provide a validation of the Arabic version of the C‐19ASS and to explore the association between the C‐19ASS and psychological symptoms syndrome.MethodIn Study 1, a community sample of 404 participants completed the Arabic version of the C‐19ASS and results were subjected to an exploratory factor analysis. In Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The current systematic review and meta-analysis sought to investigate the correlates and psychometric properties of the C-19ASS. The C-19ASS exhibited a consistent factor structure and acceptable reliability in Brazilian (Coelho et al, 2022), Chinese (Xin et al, 2022), Greek (Seydavi et al, Unpublished), Indonesian (Muthiah et al, 2022), Iranian (Akbari, Seydavi, et al, 2021), Italian (Mansueto et al, 2022), Saudi Arabian (Alhakami et al, 2023), Turkish (Obu ca et al, Unpublished) and US (Nikčevi c & Spada, 2020) populations. In addition, it has been studied concerning a vast array of variables, as described above, which makes it a promising tool for assessing COVID-19-pandemic-related psychopathology.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The current systematic review and meta-analysis sought to investigate the correlates and psychometric properties of the C-19ASS. The C-19ASS exhibited a consistent factor structure and acceptable reliability in Brazilian (Coelho et al, 2022), Chinese (Xin et al, 2022), Greek (Seydavi et al, Unpublished), Indonesian (Muthiah et al, 2022), Iranian (Akbari, Seydavi, et al, 2021), Italian (Mansueto et al, 2022), Saudi Arabian (Alhakami et al, 2023), Turkish (Obu ca et al, Unpublished) and US (Nikčevi c & Spada, 2020) populations. In addition, it has been studied concerning a vast array of variables, as described above, which makes it a promising tool for assessing COVID-19-pandemic-related psychopathology.…”
Section: Discussionmentioning
confidence: 95%
“…More than 62.5% used a convenience sample for participant recruitment or did not report their method of recruitment, and about 50% of the articles did not report the exclusion rate of participants. ranging from 0.02 (Nikčevi c & Spada, 2020) to 0.06 (Muthiah et al, 2022), root mean square error of approximation (RMSEA) ranging from 0.02 (Mansueto et al, 2022;Nikčevi c & Spada, 2020) to 0.07 (Akbari, Seydavi, et al, 2021;Muthiah et al, 2022), comparative fit index (CFI) ranging from 0.95 (Coelho et al, 2022) to 0.99 (Mansueto et al, 2022) and Tucker-Lewis's index (TLI) ranging from 0.90 (Muthiah et al, 2022) to 0.99 (Alhakami et al, 2023). In addition, a…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…(Alhakami et al, 2023). The EFA showed that item 4 loaded onto the Avoidance factor (Alhakami et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Since the C-19ASS was first published in English (Nikčevi c & Spada, 2020), several countries have welcomed it, including Iran (Persian; Akbari et al, 2022), Italy (Italian;Mansueto et al, 2022), Indonesia (Indonesian; Muthiah et al, 2022), Brazil (Portuguese;Coelho et al, 2022), Saudi Arabia (Alhakami et al, 2023), and Canada (Seth et al, 2023). It has been shown, as a measure, to have a strong structure (confirmed two factors), convergent (with functional impairment as measured by work and social adjustment; Mundt et al, 2002), and divergent (from generalized anxiety, Akbari et al, 2022; negative affect and coronavirus anxiety scale; Lee et al, 2020) validity and incremental validity in explaining additional variance in the work and social adjustment scale (Mundt et al, 2002), and coronavirus anxiety scale (Lee et al, 2020).…”
Section: Aim Of the Current Studymentioning
confidence: 99%